Looking before Leaping: Creating a Software Registry. Issue 1 (23rd November 2015) - Allen, Alice; Schmidt, Judy
What lessons can be learned from examining numerous efforts to create a repository or directory of scientist-written software for a discipline? Astronomy has seen a number of efforts to build such a resource, one of which is the Astrophysics Source Code Library (ASCL). The ASCL (ascl.net ) was founded in 1999, had a period of dormancy, and was restarted in 2010. When taking over responsibility for the ASCL in 2010, the new editor sought to answer the opening question, hoping this would better inform the work to be done. We also provide specific steps the ASCL is taking to try to improve code sharing and discovery in astronomy and share recent improvements to the resource.